A Review of YouTube for Tourism Promotion in Indonesia - D Damiasih; Arneta Rohma Agustina; Azril Azahari; Dwiyono Rudi Susanto (IJISTECH (International Journal of Information System and Technology), 2021)
Currently, YouTube as one os popular social media platrom is something that has potential as a medium for tourism promotion. This is because YouTube is a social media that has the second largest number of users, it can also be an effective media for promotion since YouTube displays visual and audio that are considered to be attractive. Hence, it can contribute to grow and increase the interest of tourists to visit. This has been proven by several countries that tourism sectors have become famous since the videos uploaded through the YouTube. There are several things that must be considered by Indonesia in making tourism promotional videos. Therefore, this paper presents a review on the usage of Youtube as platform for tourism promotion made by many scholars in Indonesia. This paper further presents a discussion on what should tourims business player should do on their YouTube promotion channel. Finally, we present open problems for future research recommendations.